An improved model for the surface potential and drain current in negative capacitance field effect transistors. Issue 105 (31st October 2016) - Xiao, Y. G.; Ma, D. B.; Wang, J.; Li, G.; Yan, S. A.; Zhang, W. L.; Li, Z.; Tang, M. H.
Abstract : An improved model for the surface potential and drain current in negative capacitance ferroelectric field effect transistors (NC-FeFETs) was presented by introducing the doping concentration. Abstract : An improved model for the surface potential and drain current in negative capacitance ferroelectric field effect transistors (NC-FeFETs) was presented by introducing the doping concentration. The influence of the doping concentration and temperature on the electric characteristics of NC-FeFET was investigated based on this model. The derived results demonstrated that the subthreshold slope of the metal–ferroelectric–semiconductor NC-FeFET increases, while the drive current decreases when the substrate doping concentration increases from 10 17 m −3 to 10 20 m −3 . Additionally, in the temperature range from 290 K to 380 K, the voltage amplification gradually shrinks, resulting in the subthreshold swing increasing from 51 mV dec −1 to 71 mV dec −1 . These results indicated that silicon doping concentration and temperature are two key factors for optimizing the operation voltage in NC-FeFETs.